Kewajiban Pembayaran Royalti atas Cover Lagu Perspektif Fatwa DSN Nomor 1 Tahun 2003 Tentang Hak Cipta (Studi Kasus YouTuber di Kota Medan) - Husna, Shofia; Permata, Cahaya (UNES Law Review, 2023)
A song cover is the activity of repeatedly singing another person's song and then releasing it as a new recording. YouTube monetization means that many people often cover other people's songs to increase viewers and subscribers, so many people cover other people's songs to get monetization or income from YouTube. The purpose of this research is to find out the reasons why YouTubers in the city of Medan cover songs, to find out the law on royalty payments for the act of covering songs based on DSN Fatwa Number 1 of 2003 concerning Copyright, and the implementation of regulations on the obligation to pay royalties for song covers on YouTube media by YouTubers in Medan city. The research method used is empirical juridical research using a statutory approach and case studies. This research is a descriptive analysis. Data was collected through observation, interviews, and document study. The results of this research show that the reasons why YouTubers in the city of Medan cover songs are varied, namely for commercial and non-commercial purposes. The obligation to pay royalties for song covers is based on DSN Fatwa No. 1 of 2003 concerning Copyright, it is said to be a violation if you perform, reproduce, record, distribute, or publish a song belonging to another person, especially for commercial purposes. However, if it does not have a commercial purpose and you have asked permission first from the copyright holder and include the name of the original owner, then the cover of the song is permitted and you are not required to pay royalties.